1993
DOI: 10.1071/wr9930495
|View full text |Cite
|
Sign up to set email alerts
|

Ecology of the rufous hare-wallaby, Lagorchestes hirsutus Gould (Marsupialia : Macropodidae) in the Tanami Desert, Northern Territory. III Interactions with introduced mammal species.

Abstract: This paper reports a study of the interactions between a remnant population of the rufous hare-wallaby, Lagorchestes hirsutus, and populations of several introduced mammal species in a region of the Tanami Desert. Transect counts of faecal pellets and tracks were used to determine the local distributions of all species and analysis of faeces from both predators and competitors of hare-wallabies was undertaken. Six species of introduced mammals were recorded within the study area: dingoes, rabbits, camels, foxe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
50
0

Year Published

1996
1996
2014
2014

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(50 citation statements)
references
References 0 publications
0
50
0
Order By: Relevance
“…It has also been noted that cats can increase in density following the removal of dingoes (Lundie-Jenkins et al, 1993;Pettigrew, 1993 ;Christensen & Burrows, 1995). Using data presented by Catling & Burt (1994), Dickman (1996 b) calculated that there was a negative correlation between the abundance of dingoes and feral cats in southern New South Wales.…”
Section: Evidence For Interactions (1 ) Interactions Between Natmentioning
confidence: 99%
See 2 more Smart Citations
“…It has also been noted that cats can increase in density following the removal of dingoes (Lundie-Jenkins et al, 1993;Pettigrew, 1993 ;Christensen & Burrows, 1995). Using data presented by Catling & Burt (1994), Dickman (1996 b) calculated that there was a negative correlation between the abundance of dingoes and feral cats in southern New South Wales.…”
Section: Evidence For Interactions (1 ) Interactions Between Natmentioning
confidence: 99%
“…Control of dingoes may have allowed invasion of the area by foxes (Short, Kinnear & Robley, 2002). Lundie-Jenkins et al (1993) also reported the absence of foxes from their central Australian study area until dingoes were removed by poisoning. A single fox was then believed responsible for the extinction of a local population of endangered rufous harewallabies (Lagorchestes hirsutus).…”
Section: Evidence For Interactions (1 ) Interactions Between Natmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, studies conducted over small spatial scales may acquire severely biased results. For example, the areas sampled in [109] or [110] were very small (<10km2), which likely represented only a fraction of a dingo's home range in such systems [111,112]. The observed relationships between species within such small areas may have limited applicability outside the areas sampled, where animal abundances may be markedly different (e.g.…”
Section: Sampling Biasmentioning
confidence: 99%
“…It was stated by Priddel & Wheeler (1994) that 'without effective fox control, further extinction of remaining populations of ?Aalleefowl within the New South Wales wheatbelt appears inevitable. ' The use of 1080 baits to control foxes is increasing greatly in fauna reintroduction and management programs in Australia (Friend 1990;Kinnear et al 1988;Lundie-Jenkins et al 1993;Short & Smith 1994). Foxes are very sensitive to 1080 (McIlroy & King 1990), whereas some native fauna in Australia have developed very high tolerances to the toxin (Twigg & King 1991).…”
Section: Emumentioning
confidence: 99%